Two-way multiple-antenna relaying with and without binary network coding - Eslamifar, Mahshad (2010)
Two-step bi-directional communication between two users communicating with each other via a central wireless relay node (or nodes) can be achieved by using multiple antennas and network coding in conjunction at the relay. In this thesis, we begin by analyzing six different multi-antenna relaying schemes with binary or analog network coding for bi-directional relaying, considering a dual-antenna relay node and two single-antenna user nodes. The relaying schemes with analog network coding are Transmit Beamforming (TB) and Antenna Selection (AS). The relaying schemes with binary network coding are Binary Network Coding (BNC), space-time block code with binary network coding (STBC-BNC), Antenna Selection with binary network coding (AS-BNC) and Max-Min Antenna Selection with binary network coding (Max-Min AS-BNC). We derive the diversity order and symbol error probability formulas of these bi-directional relaying schemes. Next, we consider bi-directional relaying using multiple relays with Max-Min Antenna Selection, and we analyze the performance in terms of outage probability. We show that better performance is achieved by spreading out the antennas among the relays, rather than having relays with more antennas. Finally, considering correlated relay antennas, we analyze the outage probability of bi-directional relaying as a function of rate, average SNR, number of relays, number of antennas per relay and correlation coefficient, and we derive the number of relays required to have a specific outage probability.